Short-term feeding of Aureomycin (R) to suppress the occurrence of respiratory diseases in cattle. - Koch, B.A.; Smith, E.F.; Richardson, D.; Cox, R.F.; Hay, W.H.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
One of the major problems confronting cattlemen is control of occurrence of respiratory diseases such as the shipping fever complex, colds, nasal congestion, and pneumonia. These respiratory conditions .are especially troublesome to the cattle feeder who ships and receives cattle during the fall and winter months when adverse weather conditions create added stress on cattle. It is the purpose of this study to investigate the value of orally administering antibiotics to weaning calves to control the occurrence of respiratory diseases during the first 28 days they are in the dry-lot.
Keywords: Beef; Aureomycin; Respiratory diseases